Impact of Raised Blood Glucose Level on In-Hospital Outcome of Thrombolysed Patients with Acute Myocardial Infarction (Bangladesh Heart Journal, 2020)
Background: Diabetes mellitus (DM) is an established major cardiovascular risk factor associated with increased prevalence of coronary artery disease (CAD). Patients with diabetes often have numerous concomitant cardiac risk factors with a higher incidence of acute myocardial infarction (AMI) and congestive heart failure (CHF). Patients either with or without a prior history of DM may present with hyperglycemia during AMI. We analysed our population to determine whether admission hyperglycemia was a strong risk factor for in-hospital mortality and morbidity in patients with AMI and may be even stronger than a previous history of diabetes.In-hospital death risk of AMI patients without DM was about 2 to 4 times higher in patients with hyperglycemia than in those without hyperglycemia.Methods: This Prospective observational study was carried out at the National Institute of Cardiovascular Diseases (NICVD), Dhaka. A total number of 200 STsegment elevation AMI patients were enrolled in this study as per inclusion and exclusion criteria. They were subdivided on the basis of admission blood glucose into two groups. Group-1A and 2A were 50 patients with blood glucose